48.2k views
5 votes
Complete the recursive formula of the arithmetic sequence –3,-1,1,3,....

User Guruku
by
5.6k points

2 Answers

3 votes
5 7 9 11 13 15 Is the next answer
User LiKui
by
5.0k points
2 votes

Answer:

b(1)=-3

b(n)=b(n−1)+2

Explanation:

Given the sequence −3,−1,1,3,...

We can infer that the first number of the sequence is -3, and the difference is +2

b(1)=first number of the sequence

b(n)=b(n−1) diffrence

If we fill this in, we get:

b(1)=-3

b(n)=b(n−1)+2

User XylemFlow
by
4.9k points